No safe haven: Protection levels show imperilled South African reptiles not sufficiently safe-guarded despite low average extinction risk. (May 2019) - Tolley, Krystal A.; Weeber, Joshua; Maritz, Bryan; Verburgt, Luke; Bates, Michael F.; Conradie, Werner; Hofmeyr, Margaretha D.; Turner, Andrew A.; da Silva, Jessica M.; Alexander, Graham J.
Abstract: Compared to the global average, extinction risk for mainland African reptiles, particularly for South Africa, appears to be relatively low. Despite this, African reptiles are under threat primarily due to habitat loss as a result of agriculture, resource extraction, and urbanisation, and these pressures are expected to increase into the future. South Africa's reptile fauna is relatively well-studied, allowing an investigation of whether threat status assessment limitations are driving the comparably low threat status for the country, a large component of Africa's reptile fauna (ca. 25% of mainland African reptiles are found in South Africa). Extinction risk of South African reptiles was assessed as of 2018 using IUCN criteria and we 'backcast' these assessments to infer extinction risk circa 1990. A Red List Index (RLI: a measure of the extinction risk for a group of species) for 1990 and 2018 was estimated, and the protection level afforded to South African reptiles was investigated by intersecting reptile distributions with the network of protected areas. Finally, a coarse estimate of extinction rate was made. Level of extinction risk for South African reptiles (ca. 5.4%) is lower than the global average, and most currently threatened species would have already been at risk by 1990. The RLI was slightly lower for 2018 than for 1990, and the decrease was more prominent for endemic reptiles than for all reptiles combined. Most South African reptiles fall into the Well Protected category, implying that the protected area network has substantial conservation impact. However, many threatened reptile species are Poorly Protected or Not Protected. The current extent of the protected area network therefore, does not adequately mitigate extinction risk for reptiles. Furthermore, the protected area expansion plan for South Africa would not capture any additional threatened species within its boundaries. Despite the lower level of extinction risk indicated by IUCN assessments, it would be premature to assume that South African reptiles are faring better than reptiles globally based only on this one measure. Notably, two South African reptiles are Critically Endangered and theses are not found in protected areas, two others are already classified as Extinct, and rough estimates of extinction rates are similar to values estimated for other vertebrates. By considering additional metrics that are directly guided by our in-depth knowledge of the species, their distributions and the threats, we demonstrate that South African reptiles are under pressure and that risk of extinction is tangible for several species.